The history of music in fifty instruments - Wilkinson, Philip, 1955- (Firefly Books, 2014)
Wilkinson charts the evolution of musical instruments, profiling the instruments that have joined the orchestra from the Baroque era of the 1600s up to the modern age. The origin and development of each instrument is described. Includes brief information on the instrument makers, composers, and musicians who have made them famous.